Right heart function deteriorates in breast cancer patients undergoing anthracycline-based chemotherapy - Boczar, Kevin E.; Aseyev, Olexiy; Sulpher, Jeffrey; Johnson, Christopher; Burwash, Ian G.; Turek, Michele; Dent, Susan; Dwivedi, Girish (Université d'Ottawa | University of Ottawa, 2016)
Abstract Background: Cardiotoxicity from anthracycline-based chemotherapy is an important cause of early and late morbidity and mortality in breast cancer patients. Left ventricular (LV) function is assessed for patients receiving anthracycline-based chemotherapy to identify cardiotoxicity. However, animal studies suggest that right ventricular (RV) function may be a more sensitive measure to detect LV dysfunction. The purpose of this pilot study was to determine if breast cancer patients undergoing anthracycline-based chemotherapy experience RV dysfunction. Methods: Forty-nine breast cancer patients undergoing anthracycline-based chemotherapy at the Ottawa Hospital between November 2007 and March 2013 and who had 2 echocardiograms performed at least 3 months apart were retrospectively identified. Right atrial area (RAA), right ventricular fractional area change (RV FAC) and RV longitudinal strain of the free wall (RV LSFW) were evaluated according to the American Society of Echocardiography guidelines. Results: The majority (48/49) of patients were females with an average age of 53.4 (95% CI: 50.1-56.7 years). From baseline to follow-up study, average LV ejection fraction (LVEF) decreased from 62.22 (95% CI: 59.1-65.4) to 57.4% (95% CI: 54.0-60.9) (P = 0.04). During the same time period, the mean RAA increased from 12.1 cm2 (95% CI: 11.1-13.0 cm2) to 13.8 cm2 (95% CI: 12.7-14.9 cm2) (P = 0.02), mean RV FAC decreased (P = 0.01) from 48.3% (95% CI: 44.8-51.74) to 42.1% (95% CI: 38.5-45.6%), and mean RV LSFW worsened from -16.2% (95% CI: -18.1 to -14.4%) to -13.81% (95% CI: -15.1 to -12.5%) (P = 0.04). Conclusion: This study demonstrates that breast cancer patients receiving anthracycline-based chemotherapy experience adverse effects on both right atrial size and RV function. Further studies are required to determine the impact of these adverse effects on right heart function and whether this represents an earlier marker of cardiotoxicity.